Research on the Differences of Outdoor Sound Perception and Sound Preference between Urban and Rural Residential Areas - Jun Zhang, Tingting Li, Peng Cui, Qing Yin, Chunyu Dai (Forest Chemicals Review, 1970)
In this study, it has investigated the residents’ sound perceptions to outdoor sound sources in urban and rural residential areas by means of field measurements and questionnaire surveys, in which it analyzed the differences in sound perceptions and sound preferences of urban and rural residents, laying a sound foundation for subsequent soundscape designs for people of different socioeconomic status. The study demonstrated that the sound pressure levels (abbreviated as“SPL”) of the third floor in the countryside was lowest. The SPL from the first floor to the second floor in cities declined gradually floor by floor. Whereas, the SPL from the second floor to the third-floor climbed layer by layer. The disparities in the sound sources in urban and rural residential areas contributed to the distinctions of the sound source recurrence rate between urban and rural residents. Rural residents’ favorite was the sound of music, while urban residents’ favorite was the sound of birds. There is a correlation at p≤0.05 or p≤0.01 between residents’ gender, age, educational level, individual sound source and his/her sound preference evaluation. However, economic factors are not related to the resident’s sound preference evaluation but affect it indirectly.